Implementasi Konsep Feel the Art Through the Office pada Interior Kantor Popo Danes Architect dan Melati Danes Space and Style Bali - Fiona, Adelia; Sitindjak, Ronald Hasudungan Irianto (Intra, 2017)
Popo Danes Architecture and Melati Danes Space and Style office is one of the architect and interior consultant office in Bali. The office still applies Balinese traditions in its design. In the room division there are some rooms that are not used in accordance with its function, making it difficult for employees to interact and work productively. Therefore, the concept of feel the art through the office that can answer the problems of the office. So with the concept is expected to be more comfortable and efficient for employees while working in the office of Popo Danes Architect and Melati Danes Space and Style. Futhermore, with this design can increases the number of requests for the services of architect or interior services because the client likes the design of Popo Danes Architect and Melati Danes Space and Style office.